Simulation Genres and Student Uptake: The Patient Health Record in Clinical Nursing Simulations. (July 2017) - Campbell, Lilly
Drawing on fieldwork, this article examines nursing students' design and use of a patient health record during clinical simulations, where small teams of students provide nursing care for a robotic patient. The student-designed patient health record provides a compelling example of how simulation genres can both authentically coordinate action within a classroom simulation and support professional genre uptake. First, the range of rhetorical choices available to students in designing their simulation health records are discussed. Then, the article draws on an extended example of how student uptake of the patient health record within a clinical simulation emphasized its intertextual relationship to other genres, its role mediating social interactions with the patient and other providers, and its coordination of embodied actions. Connections to students' experiences with professional genres are addressed throughout. The article concludes by considering initial implications of this research for disciplinary and professional writing courses.